Soil Symbiosis Reimagined: Rhizobium and Mycorrhiza Influence on Soybean Performance in Early Oil Palm Ecosystems - Anugraeni Rahman, Reski; Weny Respatie, Dyah; Tarwaca Susila Putra, Eka; Laurenze, Reynaldi (HAYATI Journal of Biosciences, 2025)
The high demand for soybeans in Indonesia is not in line with national soybean production due to the harvest area decreasing every year. To increase national soybean production, the area of IOP (Immature Oil Plantation) one year has potential for soybean development. This study aimed to investigate the effect of Rhizobium spp. and arbuscular mycorrhizal fungi (AMF) inoculation on the physiological capacity, growth, and yield of the soybean plant planted between rows of IOP one-year-old. This research was carried out at PT Perkebunan Nusantara IV (PTPN IV), Adolina Afdeling 1, Serdang Bedagai Regency, North Sumatra, from March 2023 to June 2023. A two-factor Randomized Complete Block Design (RCBD) with four replications for all treatments was conducted in a field experiment. Experimental treatments include: 1) non-inoculated Rhizobium spp. + non-inoculated AMF (R0M0) (Control), 2) non-inoculated Rhizobium spp. + inoculation AMF (R0M1), 3) inoculation Rhizobium spp. + non-inoculated AMF (R1M0) and 4) inoculation Rhizobium spp. + inoculation AMF (R1M1). The results showed that the single arbuscular mycorrhizal fungi (AMF) inoculation treatment significantly enhanced soybean physiology, growth, and yield including relative water content (85.87%), nitrate reductase activity (8.98 µmol NO2-g BS-1 hour-1), stomatal density (775.16 mm), proline (17.76 µmol proline g BS-1), and ascorbate peroxidase (0.0068 U/min/mg).